Impoliteness Utterances in Column Comment Chaitlyn's Posts on Instagram: Pragmatics Approach - Ika Wijayanti; Zia Hisni Mubarak (Asosiasi Ide Bahasa Kepri, 2020)
This research aimed to describe an aspect of impoliteness found in utterances in the form of comments that contained impoliteness strategies specifically found in comment columns, theory about the aspects of impoliteness strategies purposed by Culpeper. The main instrument in this research was the context in utterances written by haters in comment columns. Then, it made this study used a pragmatic identity method to analyze data due it focused on utterances from haters. In addition, the design of this research was qualitative descriptive because this study described impoliteness strategy in words only. Indeed, researcher used non-participant technique to collect the data in screenshots. The last is an informal method used in this study, researcher used this method to present data in text form. The results of this study were only four strategies from five strategies by Culpeper that used by haters while commenting the posts. There were, positive impoliteness strategy, negative impoliteness strategy, bald on record strategy, mocking politeness or sarcasm, but withhold politeness strategy which was not applied by hatters. In addition, there are five causes which trigger hatters used impoliteness strategies while giving comments, there are fake accounts, sexual harassment, emotions, environment, and LGBT problems.